2019
DOI: 10.1080/10715762.2019.1624741
|View full text |Cite
|
Sign up to set email alerts
|

Formation of methyl radicals derived from cumene hydroperoxide in reconstructed human epidermis: an EPR spin trapping confirmation by using13C-substitution

Abstract: Dermal exposure to cumene hydroperoxide (CumOOH) during manufacturing processes is a toxicological issue for the industry. Its genotoxicity, mutagenic action, ability to promote skin tumor, capacity to induce epidermal hyperplasia and aptitude to induce allergic and irritant skin contact dermatitis are well known. These toxic effects appear to be mediated through the activation to free radical species such as hydroxyl, alkoxyl and alkyl radicals characterized basically by electron paramagnetic resonance (EPR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…To overcome this, one possibility is to carry out spin‐trapping studies with target compounds site‐specific labelled with 13 C at positions precursors of potentially reactive radicals. Recent EPR‐ST studies with cumene hydroperoxide 13 C‐substituted at methyl positions confirmed the trapping of methyl radicals released by decomposition of the hydroperoxide in the RHE model 27 …”
Section: Current Knowledge About the Sensitizing Capacity And The Dia...mentioning
confidence: 91%
See 1 more Smart Citation
“…To overcome this, one possibility is to carry out spin‐trapping studies with target compounds site‐specific labelled with 13 C at positions precursors of potentially reactive radicals. Recent EPR‐ST studies with cumene hydroperoxide 13 C‐substituted at methyl positions confirmed the trapping of methyl radicals released by decomposition of the hydroperoxide in the RHE model 27 …”
Section: Current Knowledge About the Sensitizing Capacity And The Dia...mentioning
confidence: 91%
“…Recent EPR-ST studies with cumene hydroperoxide 13 C-substituted at methyl positions confirmed the trapping of methyl radicals released by decomposition of the hydroperoxide in the RHE model. 27 In conclusion, we can see that radicals formed from hydroperoxides are key intermediates that could explain the reactivity with skin proteins and, therefore, their sensitizing potential. Moreover, we now know that these intermediates are formed in a 3D model of the epidermis, under conditions closer to what may occur in vivo.…”
Section: Methodsmentioning
confidence: 99%
“…This needed to further optimize the concentrations of products used in order to achieve the best S/N ratio. 90 To identify radical intermediates potentially involved in skinsensitization processes, this methodology has been further successfully applied to skin sensitizers such as endoperoxide Asc, 91 and ROOHs derived from autoxidation of linalool, 85 limonene, 86 or citronellol. We quickly noticed that concentrations of spin trap and ROOH needed in the case of EPR-ST studies in RHE are, in general, at least 10-fold higher than those giving a good S/N ratio signal in solution, yet still within the typical range of clinical ACD diagnostic tests.…”
Section: Epr-st In Reconstructed Human Epidermismentioning
confidence: 99%
“…As an example, our EPR-ST studies in RHE with Cum-OOH with 13 C-substitution at methyl positions confirmed the presence of methyl radicals issued from decomposition of the hydroperoxide in the epidermis model (Figure 12). 90…”
Section: Epr-st In Reconstructed Human Epidermismentioning
confidence: 99%
“…Keratinocytes could be involved by determining the effective dose and contributing maturation signals. Focusing on keratinocytes and the early events of hydroperoxide activation, we reported lately the generation of radicals by linalool hydroperoxides and cumene hydroperoxide in situ using reconstructed human epidermis (RHE) 13,40 . Here we evaluated the individual responsiveness and magnitude of DC maturation by important hydroperoxides in 2D and 3D coculture models with keratinocytes.…”
Section: Different Potentials Of Limonene-1-ooh and Limonene-2-ooh Inmentioning
confidence: 99%